CAD-LT score effectively predicts risk of significant coronary artery disease in liver transplant candidates - Rachwan, Rayan Jo; Kutkut, Issa; Timsina, Lava R.; Bou Chaaya, Rody G.; El-Am, Edward A.; Sabra, Mohammad; Mshelbwala, Fakilahyel S.; Rahal, Mahmoud A.; Lacerda, Marco A.; Kubal, Chandrashekhar A.; Fridell, Jonathan A.; Ghabril, Marwan S.; et al. (Journal of hepatology, 2021)
Patients with cirrhosis and significant coronary artery disease (CAD) are at risk of peri-liver transplantation (LT) cardiac events. The coronary artery disease in liver transplantation (CAD-LT) score and algorithm aim to predict the risk of significant CAD in LT candidates and guide pre-LT cardiac evaluation. Patients who underwent pre-LT evaluation at Indiana University (2010-2019) were studied retrospectively. Stress echocardiography (SE) and cardiac catheterization (CATH) reports were reviewed. CATH was performed for predefined CAD risk factors, irrespective of normal SE. Significant CAD was defined as CAD requiring percutaneous or surgical intervention. A multivariate regression model was constructed to assess risk factors. Receiver-operating curve analysis was used to compute a point-based risk score and a stratified testing algorithm. A total of 1,771 pre-LT patients underwent cardiac evaluation, including results from 1,634 SE and 1,266 CATH assessments. Risk-adjusted predictors of significant CAD at CATH were older age (adjusted odds ratio 1.05; 95% CI 1.03–1.08), male sex (1.69; 1.16–2.50), diabetes (1.57; 1.12–2.22), hypertension (1.61; 1.14–2.28), tobacco use (pack years) (1.01; 1.00–1.02), family history of CAD (1.63; 1.16–2.28), and personal history of CAD (6.55; 4.33–9.90). The CAD-LT score stratified significant CAD risk as low (≤2%), intermediate (3% to 9%), and high (≥10%). Among patients who underwent CATH, a risk-based testing algorithm (low: no testing; intermediate: non-invasive testing vs. CATH; high: CATH) would have identified 97% of all significant CAD and potentially avoided unnecessary testing (669 SE [57%] and 561 CATH [44%]). The CAD-LT score and algorithm (available at www.cad-lt.com) effectively stratify pre-LT risk for significant CAD. This may guide more targeted testing of candidates with fewer tests and faster time to waitlist. The coronary artery disease in liver transplantation (CAD-LT) score and algorithm effectively stratify patients based on their risk of significant coronary artery disease. The CAD-LT algorithm can be used to guide a more targeted cardiac evaluation prior to liver transplantation. [Display omitted] •CAD-LT score guides preoperative evaluation process for liver transplantation.•Score predicts risk of significant coronary artery disease in transplant candidates.•Score is an easy-to-use clinical tool; can be employed in an office-based setting.•Algorithm detects significant coronary artery disease with high sensitivity (97%).•Algorithm provides a cost-effective approach to preoperative cardiac evaluation.